2015
DOI: 10.1371/journal.pone.0125943
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Different Levels of Adaptive Iterative Dose Reduction 3D on Image Quality of 320-Row Coronary CT Angiography: A Clinical Trial

Abstract: PurposeThe aim of this study was the systematic image quality evaluation of coronary CT angiography (CTA), reconstructed with the 3 different levels of adaptive iterative dose reduction (AIDR 3D) and compared to filtered back projection (FBP) with quantum denoising software (QDS).MethodsStandard-dose CTA raw data of 30 patients with mean radiation dose of 3.2 ± 2.6 mSv were reconstructed using AIDR 3D mild, standard, strong and compared to FBP/QDS. Objective image quality comparison (signal, noise, signal-to-n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
2
10
1
Order By: Relevance
“…In fact, there was only one case of a high-pitch spiral acquisition in this previous study. Like other studies, the SNR correlated inversely with the SAIR, which showed objective reduction in metal related image noise 14 , 15 .…”
Section: Discussionsupporting
confidence: 77%
“…In fact, there was only one case of a high-pitch spiral acquisition in this previous study. Like other studies, the SNR correlated inversely with the SAIR, which showed objective reduction in metal related image noise 14 , 15 .…”
Section: Discussionsupporting
confidence: 77%
“…To the best of our knowledge, there is only one study that has investigated the image quality of CTCA with automatic exposure control system and standard AIDR3D [ 9 ], no previous study evaluated the effect of CTCA with ATCM and strong AIDR3D. Study of Feger [ 15 ] with 320-slice CTCA showed that, strong AIDR3D had the lowest noise, the best signal-to-noise ratio (SNR) and contrast-to-noise ratio (CNR), compared with standard AIDR3D, mild AIDR3D, and FBP with quantum denoising software. Thus, the purpose of our study was to prospectively investigate image quality and radiation dose of CTCA acquired with ATCM and reconstructed by strong AIDR3D by comparison with those reconstructed by standard AIDR3D and FBP.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, this effect was not very strong. A recent study of Feger et al [ 19 ] analysed the influence of AIDR 3D levels on contour sharpness parameters for CTA and did not find a relevant difference between AIDR 3D and FBP. This could be due to the different characteristics of coronary arteries and the myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac volumes were reconstructed using two methods: filtered back projection (FBP) and Adaptive Iterative Dose Reduction 3D (AIDR-3D) [ 11 ]. For the latter, the strong level was chosen, as this has been shown to yield superior objective image quality parameters compared to mild and standard levels [ 19 ]. Slice thickness was 0.5 mm with 0.25 mm slice increment.…”
Section: Methodsmentioning
confidence: 99%